Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1371/journal.pone.0232588
|View full text |Cite
|
Sign up to set email alerts
|

Cash assistance programming and changes over time in ability to meet basic needs, food insecurity and depressive symptoms in Raqqa Governorate, Syria: Evidence from a mixed methods, pre-posttest

Abstract: Raqqa Governorate has been grappling with dual crisis-related burdens from the civil conflict and ISIS occupation. As part of a response to support households within this area, a three-month, unconditional cash assistance program was implemented by the International Rescue Committee to help households meet their basic needs. A quantitative, preposttest with 512 women at baseline (n = 456 at endline) was conducted in northern Raqqa Governorate between March-August 2018 to determine their experiences in this cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“… 31 Likewise, evidence suggested that short-term emergency UCTs (monthly transfer of US$76 for 3 months) yielded significant improvements in food security in the Raqqa Governorate. 36 In contrast, another monthly UCT (US$84 for 5 months) combined with a once-only distribution of a non-food-items kit and provision of piped water in Somalia found conflicting results when assessing its impact on acute malnutrition among children 6–59 months. Adjusted for age and sex, the intervention did not appear to reduce risk of acute malnutrition (HR 0.94, 95% CI 0.51 to 174) but did seem to increase the child dietary diversity score by 0.53 (95% CI 0.01 to 1.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 Likewise, evidence suggested that short-term emergency UCTs (monthly transfer of US$76 for 3 months) yielded significant improvements in food security in the Raqqa Governorate. 36 In contrast, another monthly UCT (US$84 for 5 months) combined with a once-only distribution of a non-food-items kit and provision of piped water in Somalia found conflicting results when assessing its impact on acute malnutrition among children 6–59 months. Adjusted for age and sex, the intervention did not appear to reduce risk of acute malnutrition (HR 0.94, 95% CI 0.51 to 174) but did seem to increase the child dietary diversity score by 0.53 (95% CI 0.01 to 1.05).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Raqqa Governorate, grappling with a dual crisis from the Islamic State of Iraq and Syrian occupation and civil conflict, found that an UCT (US$228 over 3 months) implemented by the IRC resulted in no change in perceived serious household needs and daily stressors (β=0.12; 95% CI −0.24 to 0.48) and an increase in depressive symptoms (β=0.89; 95% CI 0.34 to 1.43) before and after cash distribution. 36 Additionally, a study in Northern Uganda that combined cash transfers with business skills training indicated that there was no significant alleviation in depression. 38 Poor communication about logistics and timing of cash transfers ending, caused stress and anxiety among participants and their relationships.…”
Section: Resultsmentioning
confidence: 99%
“…Host community resentment can arise as a result, but may also emerge if IDPs receive special assistance due to their status as such ( Quintero and Culler, 2009 ). Nonetheless, the economic roots of many IDP health problems point to a need for economic empowerment of IDPs ( Amodu et al., 2020 ), including through cash transfer programmes to meet basic needs ( Falb et al., 2020 ). In general, given the limited resources available, any IDP health interventions in LMICs must also be low-cost and community-based ( Falb et al., 2020 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Nonetheless, the economic roots of many IDP health problems point to a need for economic empowerment of IDPs ( Amodu et al., 2020 ), including through cash transfer programmes to meet basic needs ( Falb et al., 2020 ). In general, given the limited resources available, any IDP health interventions in LMICs must also be low-cost and community-based ( Falb et al., 2020 ). For example, training IDPs as health workers in camps has sometimes proven effective ( Ehiri et al., 2014 ).…”
Section: Review Findingsmentioning
confidence: 99%
“…Given this overall largely positive, but still mixed evidence on how cash or other forms of economic empowerment [ 14 ] may reduce or exacerbate risks for women, alongside the increasing use of cash as a humanitarian intervention, the objective of this study was to better understand the impact of cash transfers in acute emergencies on women’s experiences of violence and exploitation, mental health, and economic wellbeing [ 15 ]. The study design through which this case analysis is drawn from was a quantitative pre-post test conducted with 512 women at baseline in March 2018 and 456 at endline in August 2018 (loss to follow up: 10.9%) implemented in three villages in northern Raqqa Governorate [ 15 ]. The baseline was delivered in advance of the first cash transfer; the endline survey was administered two-three weeks after the final cash disbursement as no long term impacts of cash were hypothesized.…”
Section: Introductionmentioning
confidence: 99%